The Occurrence and the Characteristics of Liver Injury, and its Impactamong Hospitalized Covid-19 Patients in Basrah City-Iraq - Fateh Al-khaqani; Yasser Alaa Sabeeh; Ali Raheem Hashim; Hassan Ala Farid (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: The respiratory system is most affected by the severe acute respiratory syndrome coronavirus2 (SARS-CoV2). However, COVID-19 can appear in a variety of ways. It has found a link between higher liverenzymes and COVID-19 infection, implying that the virus can induce liver damage through direct hepatotoxicinjury, medication toxicity, or an immune-mediated response.Materials and Methods: In the southern Iraqi province of Basra, a cross-sectional observational study is beingconducted in a single center (Basra teaching hospital) to estimate the prevalence of liver damage among hospitalizedpatients and identify those at risk.Results: The study found that most of the patients have a normal liver function test at the time of diagnosisand or admission, but after hospitalization, there is a statistically significant increase in the liver enzymes thatis positively related to the disease severity and cytokine storm and also lead to more extended hospital stayingand further mortality. Fortunately, the degree of liver damage is of mild severity in the majority of patients. Still,the severe form of liver damage was also noticed in some patients, especially those with a higher degree of lunginvolvement and severely desaturates with raised inflammatory markers.Conclusions: Elevated liver enzymes are prevalent, but the majority is mild with COVID-19 disease. Liver functionabnormalities, particularly increased levels of AST and ALT, are not only common in COVID-19, but they are alsolinked to poor outcomes, mainly if severe liver damage has occurred.